The debt crisis and the adoption of Asset-Light and Fee-Orientated (ALFO) arrangements at Marriott: 1980-1995 - John Rice; Muhammad Mustafa Raziq; Nigel Martin; Peter Fieger; Bridget Rice (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: This case study examines Marriott Corporation's large and successful spinoff between 1993 and 1995 and the concomitant adoption of a corporate ALFO strategy enabled by the transfer of assets and debt between the two entities. As an example of corporate restructuring, it involves changing ownership, operational structure, or business activities within a corporation in order to improve shareholder performance. Methods: Key directional changes in Marriott's history that have changed the structure of the business is used to examine the spinoff and ALFO strategy adaptation. Results: Marriot have been characterised by a small number of significant and foresightful innovations. There was a great deal of importance attached to the company's move away from food service and towards accommodation in the future. During the early stages of the company's existence, the company was located near Marriott's Bethesda headquarters and was headed by the founder's oldest son. There is no doubt that these investments have been probing in nature in the recent past, but they are significant in terms of scale and commitment in the future. Implications: Marriott's success can be attributed to the fact that the company has a flexible corporate strategy that focuses on high growth and high yield business opportunities, as well as the willingness to dispose of assets that don't provide this outcome. As a result of this focus, the company was able to grow globally from the 1990s onwards. Ultimately, it can be said that the company's success can be attributed to the fact that it has adapted appropriately and successfully to changing operational and industry realities over the course of many decades, especially as exigencies in the asset and debt markets rendered the portfolio structure it had developed over so many decades unsustainable.
Keywords: B1; N80; Z30; 330; Business history; Capability development; Financing models; Lodging industry